Effectiveness of native vitamin D therapy in patients with chronic kidney disease stage 3 and hypovitaminosis D in Colombia, South America (2019)
In a high percentage of patients with chronic kidney disease (CKD) low levels of vitamin D are detected. The purpose of this study was to evaluate if the native vitamin D therapy (cholecalciferol) in the patients with stage 3 and hypovitaminosis D allows to modify markers of bone and mineral metabolism once normal serum levels have been achieved.